Implementation of the Land Consolidation Program in Slum Areas in Penawangan Village, Pringapus District, Semarang Regency - Fadli, Naufal Nur; Sapardiyono, Sapardiyono; Sugiasih, Sugiasih (Sekolah Tinggi Pertanahan Nasional, 2025)
The rapid development of a region's environment has led to the emergence of slum areas due to the growing population and increased industrial and commercial activities. One way to address slum areas is through the Land Consolidation program. The implementation of land consolidation often encounters failures, so examples of successful implementation of the program are needed. This study aims to determine the stages of implementing the land consolidation program, the factors that inhibit and drive land consolidation, and the impact of land consolidation on the environmental and socio-economic conditions of the community. This study was conducted using a survey method with a mixed-method approach. Data collection methods were carried out using questionnaires, interviews, observations, and literature studies. The results of this study indicate that the implementation of land consolidation is running in accordance with applicable regulations. In its implementation, there are inhibiting and driving factors, both internal and external. Land consolidation has an impact on improving environmental quality and the socio-economic conditions of the community. The results of the implementation of land consolidation in Penawangan Village can be used as a reference for the level of success if a similar program is duplicated in a similar location and can identify efforts to overcome problems that arise later during implementation.